Flexible Tactile Sensing Systems: Challenges in Theoretical Research Transferring to Practical Applications - Yao, Zhiyu; Wu, Wenjie; Gao, Fengxian; Gong, Min; Zhang, Liang; Wang, Dongrui; Guo, Baochun; Zhang, Liqun; Lin, Xiang (Nano-Micro Letters, 2025)
Since the first design of tactile sensors was proposed by Harmon in 1982, tactile sensors have evolved through four key phases: industrial applications (1980s, basic pressure detection), miniaturization via MEMS (1990s), flexible electronics (2010s, stretchable materials), and intelligent systems (2020s-present, AI-driven multimodal sensing). With the innovation of material, processing techniques, and multimodal fusion of stimuli, the application of tactile sensors has been continuously expanding to a diversity of areas, including but not limited to medical care, aerospace, sports and intelligent robots. Currently, researchers are dedicated to develop tactile sensors with emerging mechanisms and structures, pursuing high-sensitivity, high-resolution, and multimodal characteristics and further constructing tactile systems which imitate and approach the performance of human organs. However, challenges in the combination between the theoretical research and the practical applications are still significant. There is a lack of comprehensive understanding in the state of the art of such knowledge transferring from academic work to technical products. Scaled-up production of laboratory materials faces fatal challenges like high costs, small scale, and inconsistent quality. Ambient factors, such as temperature, humidity, and electromagnetic interference, also impair signal reliability. Moreover, tactile sensors must operate across a wide pressure range (0.1 kPa to several or even dozens of MPa) to meet diverse application needs. Meanwhile, the existing algorithms, data models and sensing systems commonly reveal insufficient precision as well as undesired robustness in data processing, and there is a realistic gap between the designed and the demanded system response speed. In this review, oriented by the design requirements of intelligent tactile sensing systems, we summarize the common sensing mechanisms, inspired structures, key performance, and optimizing strategies, followed by a brief overview of the recent advances in the perspectives of system integration and algorithm implementation, and the possible roadmap of future development of tactile sensors, providing a forward-looking as well as critical discussions in the future industrial applications of flexible tactile sensors. Highlights: 1 This review presents current advances in flexible tactile sensor research from multifaceted perspectives including mechanisms, materials, structural design, and system integration. 2 It establishes performance-oriented rational design principles for sensors in practical. 3 It summarized the challenges and strategies in translating flexible tactile sensing systems into practical applications, and proposed a research roadmap for future investigations.